Quality of life of patients with coronary heart disease treated with the bioresorbable vascular scaffold (ABSORB (TM)): 2-year results from the GABI-R-registry - Pahmeier, Kathrin; Neusser, Silke; Hamm, Christian; Kastner, Johannes; Wohrle, Jochen; Zahn, Ralf; Achenbach, Stephan; Mehilli, Julinda; Gori, Tommaso; Naber, Christoph; Nef, Holger; Neumann, Till; et al. (Bmc Cardiovascular Disorders, 2022)
Background Numerous studies have reported clinical endpoints following coronary revascularization using bioresorbable vascular scaffolds (BVS), while information about the impact on health-related quality of life is sparse. In this analysis of the German-Austrian ABSORB RegIstRy, the 2 year results concerning quality of life development in a large cohort of patients treated with BVS were reported. Methods Data were collected at baseline as well as 30 days, 6 and 24 months after coronary revascularization using BVS. The EQ-5D score, EQ visual analogue scale (VAS) and Seattle Angina Questionnaire (SAQ) were determined for each time point. Patients were categorized according to the indication for coronary revascularization [acute coronary syndrome (ACS), stable angina pectoris (SAP), silent myocardial ischemia (SMI), or other]. Binary logistic regression analysis was performed to determine factors that predict above-average scores two years after implantation. Results Data from 1317 patients in 88 centres were included. Reasons for revascularization were: ACS (n = 643), SAP (n = 443), SMI (n = 52), and other (n = 179). Mean EQ-5D was significantly increased after six months, while a value comparable to baseline was found two years after implantation. EQ VAS and four of five dimensions of SAQ were significantly improved over baseline at all follow-up surveys. Particularly strong improvements were seen in SAQ scores angina frequency and quality of life. Binary regressions showed different statistically significant predictors in the respective models. Conclusions Following coronary revascularization with BVS strong decrease in self-reported angina frequency and increase of self-reported quality of life were observed with continuous improvements over two years of follow-up. Trial registration ClinicalTrials.gov Identifier: NCT02066623.
CRIS-Team WoS Importer:2022-09-02